PERAN PEMERINTAH DESA DALAM PENCEGAHAN DAN PENANGGULANGAN PENYEBARLUASAN PEKERJA SEKS KOMERSIAL (PSK) DI EKS LOKASI PROSTITUSI SUMBER LOH DESA BENELAN KIDUL - Ulum, Zebfri Bahril Ulum; Wilujeng, Sri Wilujeng; Vitasari, Leni Vitasari (JURNAL KATARSIS, 2024)
Role Of The Village Government In The Prevention And Control Of The Distribution Of Commercial Sex Workers (CSWs) In The Former Prostitution Location Of Sumber Loh Benelan Kidul Village. The purpose of this study is to determine the role of the village government in the prevention and control of the distribution of Commercial Sex Workers (CSWs) in the former prostitution location of Sumber Loh, and to find out what internal and external factors are hampering the village government in preventing and controlling the spread of CSWs in the former prostitution location Sumber Loh, Benelan Kidul Village. The results of the study show that the role of the village government in the prevention and control of the distribution of Commercial Sex Workers (CSWs) in Sumber Loh has already been carried out, such as: first the 1x24 forward must report to the local RT, data must be reported to the above village government unit once a month. Third Da'wah with a spiritual splash or routine recitation conducted at Sumber Loh. And fourthly Training or Empowerment for Benelan Kidul villagers in general. The roles are still in planning such as: firstly the empowerment effort by providing culinary tourism or a snack market near Sumber Loh. And second is the revitalization of the sports center carried out by the village government which is expected to narrow the scope of prostitution activities. While internal and external factors that hamper the role of the government are also still found. This is based on the results of interviews and observations that have been carried out, where the village head and some of his staff and elements in Sumber Loh as informants provide information to researchers for research needs.